Markov Chain Monte Carlo (MCMC) Method for Studying Magnetic Behaviors in Trinuclear Cobalt(II) Compound. Issue 11 (9th May 2018) - Wang, Quan; Li, Hang‐Xing; Wang, Kun‐Miao; Wang, Xiao; Xue, Zhe; Jia, Lei; Du, Lin; Zhao, Qi‐Hua
Abstract: A Co II coordination polymer built from a mixed azide and zwitterionic pyridinium ions and its temperature‐dependent magnetic properties are described. We used the Markov chain Monte Carlo (MCMC) method to fit the data, and found the following results: (1) there are strong correlations between the model parameters; (2) the data at above 28 K are well fitted by the magnetism model. Abstract : Behavioral problems : Two unexpected results using MCMC method were found for fitting magnetic data: (1) there was strong correlation between Landé factors and magnetic exchange parameters based on a perturbation approach by Lloret; (2) the applicable temperature range of the model formula has been determined.